(untitled) (Al-Farooq Journal of Sciences, 2026)
A field experiment was conducted during 2025/ 2026 winter season at El-Ghafara, Al-Maamorah district, Libya to study effect of five mineral nitrogen rates (0, 50, 100, 150 and 200 kg/ ha) and four bio-frtilizer inoculation treatments, i.e. control (non treated), microbein, phosphorein and microbein + phosphorein on growth and productivity of Sidi Almsry wheat variety. Randomized complete block design in split arrangement was used in three blocks, where nitrogen treatments were randomly distributed on whole plots and biofertilizer treatments were randomly occupied the sub-plots. Increasing nitrogen levels up to 200 kg/ ha produced significantly highest crop growth rate (0.149 g/ m2/ day), largest flag area (42.59 cm2), tallest plants (100.0 cm), latest heading (89.50 days after sowing) highest number of spikes and grains/ spike (355.55 m2 and 57.13 grains), respectively, heaviest 1000-kernel weight (53.14 g), maximum grain yield (7.122 t/ ha) and harvest index (38.03 %). Microbein + phosphorein treatment showed the highest crop growth rate (0.139 g/ m2/ day), largest flag leaf area (38.97 cm2), maximum number of spikes (313.58/ m2), tallest spikes (9.89 cm), maximum number of grains/ spike (51.22), heaviest 1000-grain (48.45 g) and maximum grain yield (5.505 t/ ha). Integration between 200 kg N/ ha and (microbein + phosphorein) showed the laresgt flag leaf area (43.61 cm2), tallest plants and spikes (100.56 cm and 11.65 cm), maximum number of spikes (340.07/ m2), heaviest 1000-grain weight (54.09 g) and grian yield (7.412 t/ ha) and latest heading (90.33 days). Generally, 200 kg N// ha was significantly equalled with (150 kg N/ ha combined with microbein + phosphorein) for the studied traits.